SISTEM HIMPUNAN DATA BERBASIS WEB DALAM LAYANAN BIMBINGAN DAN KONSELING - Prasetyoaji, Ari; Handayani, Sulastri (JURNAL KONSELING GUSJIGANG, 2017)
Data cumulative system is a kind of data in the guidance and counselling services which is used to help students in determining their future careers. The development of web-based data cumulative system for the guidance and counselling aims at stimulating guardians to actively participate in the guidance and counselling services done by the institution. The developed system is equipped with the short message text feature in order to facilitate staff in charge to send messages to the guardians. Web-based system to be one alternative that can reach the service to parents. This system is developed in order to stimulate the active role of parents in monitoring the development of children during the school.